Tidak Ada Hubungan Dukungan Keluarga dengan Kemandirian Personal Hygiene Anak Usia Prasekolah: There is No Relationship Between Family Support and Independence of Personal Hygiene for Preschool Children - Reni Herlinda; Hari Ghanesia Istiani; Emi Yuliza (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: The independence of preschool age children is a skill to carry out their own activities. The independence of a child can be well if the family can be tried properly. One of the benefits of the family that influences the character and behavior of children in terms of child independence is an efficient family function which includes family responses to the fulfillment of psychosocial needs, the main ones being the formation of human character, personality stability, and behavior, and the ability to carry out closer bonds and values. self. Methods: The research design used in this study is a descriptive cross-sectional correlation design. The population in this study were all parents and children aged 4-6 years in PAUD At-Taqwa Tugu Utara Cisara Bogor. The number of samples is 50 people. The sampling technique used is total sampling. The research instrument used a questionnaire. In this study, the analysis used the Chi Square test. Results: There are 45 respondents who have optimal family support and 4 respondents with non- optimal family support. Of the 45 respondents with optimal family support, 43 respondents had poor personal hygiene and 2 respondents had good personal hygiene, while from 5 respondents with inadequate family support, 4 respondents had good personal hygiene and 1 respondent had poor personal hygiene Good (Pvalue 0.276). Discussion: There is no relationship between family support and children's personal hygiene independence.